2017
DOI: 10.3389/fevo.2017.00061
|View full text |Cite
|
Sign up to set email alerts
|

From Nature to the Lab: Establishing Drosophila Resources for Evolutionary Genetics

Abstract: In recent years important tools have been developed in Drosophila to capture with the greatest possible accuracy the variation found in nature. Efforts, such as the Drosophila melanogaster Genetic Reference Panel (DGRP) or the Drosophila Synthetic Population Resource (DSPR) allied to the advances in whole-genome sequencing and analysis have propelled to unprecedented level our capacity to dissect the genotype-phenotype map. However, several practical problems arise upstream of these analyses starting with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…To ensure that data obtained in the laboratory reflect the range of possible responses found in natural populations of the species under study, the ancestral population should reflect the variability found in the field (Faria & Sucena, 2017;MacDonald & Long, 2004;Nunes et al, 2008). Several studies have used laboratory populations founded by a large number of individuals collected in the field and maintained at high numbers in the laboratory (e.g., Magalhães, Fayard, Janssen, Carbonell, & Olivieri, 2007;Martins, Faria, Teixeira, Magalhães, & Sucena, 2013;Mery & Kawecki, 2002;Teotónio, Chelo, Bradić, Rose, & Long, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…To ensure that data obtained in the laboratory reflect the range of possible responses found in natural populations of the species under study, the ancestral population should reflect the variability found in the field (Faria & Sucena, 2017;MacDonald & Long, 2004;Nunes et al, 2008). Several studies have used laboratory populations founded by a large number of individuals collected in the field and maintained at high numbers in the laboratory (e.g., Magalhães, Fayard, Janssen, Carbonell, & Olivieri, 2007;Martins, Faria, Teixeira, Magalhães, & Sucena, 2013;Mery & Kawecki, 2002;Teotónio, Chelo, Bradić, Rose, & Long, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Twenty‐five pairs of specimens were placed in separate tubes. This procedure was repeated until generation 20 to obtain full‐sibs; isofemale strains become genetically homogeneous (isogenic) after 20 generations of full‐sibs (Faria and Sucena 2017). The obtained isogenic strains (25 strains) were maintained for several experimental generations (EGs).…”
Section: Methodsmentioning
confidence: 99%
“…We used outbred (genetically variable) populations of wild type and white (w 1118 ) D. melanogaster [43]. All the stocks were reared on conventional wheat flour and agar medium under a 12h/12h light-dark cycle at 25 °C.…”
Section: Methodsmentioning
confidence: 99%